Improving precision instrument cleaning with a quality control module: implementation and outcomes - Xiong, Juan; Jiang, Wei; Wan, Wei; Zuo, Li; Tu, Ping; Rao, Dong Xia (Frontiers in Public Health, 2025)
ObjectiveTo evaluate the effectiveness of a cleaning quality control module integrated into a hospital’s Disinfection Supply Center (DSC) for improving the cleaning quality of precision surgical instruments.MethodsIn June 2023, a cleaning quality control module was implemented in our hospital’s DSC to optimize reprocessing procedures. This module recorded deviations through textual, photographic, and video records. A comparative cohort study was conducted on 3,000 instrument sets processed before (February to May 2023) and after (June to September 2023) the intervention. Additionally, 15 DCS technicians were assessed for theoretical understanding and practical proficiency. Statistical analyses compared cleaning success rates, clinical user satisfaction, and technicians’ performance.ResultsCleaning qualification rates for instrument surfaces, accessories, and lumens increased from 97.5, 96.9, and 95.8% to 99.9, 99.2, and 98.2%, respectively. ATP bioluminescence results also improved, with rates rising from 97.1, 96.2, and 94.9% to 99.1, 98.7, and 97.9%. Clinical technicians’ satisfaction rose from 91 to 99%. Technicians theoretical and operational scores improved from 89.20 ± 3.35 to 97.10 ± 1.55 and from 90.10 ± 4.33 to 97.50 ± 1.00, respectively. All differences were statistically significant (p < 0.05).ConclusionThe cleaning quality control module significantly enhanced instrument cleaning quality, improved technicians training efficiency, enhanced departmental operational efficiency, extended instrument lifespan, and improved patient safety.